Calculation of the optimal dose of anesthetic during caesarean section in pregnant women with obesity. (Pain medicine, 2016)
Currently, regional anesthesia for obstetric operations is defined as the optimal method of anesthesia in educational supplies in obstetrics of all leading medical organizations in the world (RCOG, FIGO, ACOG, AAGBI/OAA, ASA, SOAP). The study was conducted at the Kyiv Center for Perinatal and Reproductive Medicine. The study included 35 women with overweight (BMI = 33,6 ± 4,3) and uncomplicated pregnancy at the age of 18 to 40 years, operated in the gestation period of 38 to 41 weeks (mean time – 39.7 ± 0,8 weeks) under spinal anesthesia, mostly 3–4 emergency category. Comparing the results obtained when assessing hemodynamic profile, the significant difference between the rates of cardiac index and total peripheral vascular resistance in the comparison group was noted. Thus, significantly lower hemodynamic profile was observed in patients of group I. This suggests that in pregnant women with increased body mass the application of the proposed scheme of hyperbaric bupivacaine dose application is accompanied by a decrease in the incidence of hypotension by 28.4 % and as a result, significantly fewer symptoms of disorders of the central and peripheral hemodynamics.
Keywords: dose; anesthetic; caesarean section